Model PPE (Pembimbingan, Presentasi, Evaluasi) untuk Remedi Miskonsepsi IPA Siswa SMP - Rumiyati Rumiyati; Indrawati Indrawati; Yushardi Yushardi (Jurnal Pembelajaran dan Pendidikan Sains, 2017)
This article discusses about the remedial of several science misconceptions for students in Junior High School with PPE model (Peer Tutoring, Presentation, Evaluation). PPE model is the result of development model for remedial misconception from several science concepts. The purpose of this research are to describe several science misconceptions of students in Junior High School and describe the effectiveness of PPE model for overcome the students’ misconception. The research was conducted to 31 students of SMP 1 Kencong, Jember Regency, who experience misconception from several science concepts. The tecnique used to collect data are test and interview. The data analysis technique is descriptive qualitative.The result of the research shows that misconception for several concepts that happened to students are work concept (if a body have a force, it is also has work otomatically), kinetic energy concept ( if the speed of body increased three times, so the Ek becomes three times too, it is wrong ), on the concept of potential energy ( in freely falling bodies Ek = 0 and Ep windened, when the object approaches the ground. The effectiveness of the model to overcome the students’ misconception showed by students’ positive response to the implementation of remedial learning with the model and decrease the number of students who have misconception by 17% in IXA class and 13,8% in IXB class, for average of each concept. Keywords: PPE model, remediation, misconception